2009
DOI: 10.1111/j.1365-2133.2008.08886.x
|View full text |Cite
|
Sign up to set email alerts
|

Psoralen plus ultraviolet A ± interferon-α treatment resistance in mycosis fungoides: the role of tumour microenvironment, nuclear transcription factor-κB and T-cell receptor pathways

Abstract: Gene expression changes in both the tumour and the tumour microenvironment are an important determinant of treatment outcome in early-stage MF patients. Some proinflammatory factors such as NF-kappaB, inflammatory cytokines and their receptors in addition to TCR-associated molecules could be promising targets for MF treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…We are also developing clickable linkers with alternate drug release mechanisms; one limitation of this system is the requirement for UV light to initiate drug release. Though long-wavelength UV (UVA) is used for photochemotherapeutic treatment of various cancers and skin disorders,55–61 there is need for new photocleavable groups with longer absorption wavelengths and high two-photon cross sections to increase tissue penetration 62,63. The modularity of this system combined with the versatility of graft-through ROMP will enable incorporation of new cleavable linkers into bivalent-brush polymers.…”
Section: Discussionmentioning
confidence: 99%
“…We are also developing clickable linkers with alternate drug release mechanisms; one limitation of this system is the requirement for UV light to initiate drug release. Though long-wavelength UV (UVA) is used for photochemotherapeutic treatment of various cancers and skin disorders,55–61 there is need for new photocleavable groups with longer absorption wavelengths and high two-photon cross sections to increase tissue penetration 62,63. The modularity of this system combined with the versatility of graft-through ROMP will enable incorporation of new cleavable linkers into bivalent-brush polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Humme and colleagues 61 conducted an overall assessment of the many trials looking at the combination of IFN alfa and PUVA including that by Wozniak and colleagues. 60 This review pooled the results of 11 selected trials that investigated the combination of PUVA and IFN alfa, including 3 randomized controlled trials, 3 prospective cohort studies, 2 retrospective case series, 2 undefined trials, and a study that included data from a retrospective analysis as well as a prospective randomized trial. Although this review calculated a mean overall response rate of 79% AE 15% across all trials, it concluded that the addition of IFN alfa did not increase the efficacy of PUVA in patch-or plaque-stage MF.…”
Section: Interferon Alfa Alonementioning
confidence: 99%
“…In many types of malignancies the mechanism of action of proteasome blockers depends on NF‐κB inhibition and/or p53 upregulation. This has also been assumed true for CTCL, as well as other types of cancer, where the constitutive activation of NF‐κB seems to be a central mechanism of tumour cell survival and resistance to apoptosis 24,25,35,36 …”
Section: Discussionmentioning
confidence: 91%
“…This has also been assumed true for CTCL, as well as other types of cancer, where the constitutive activation of NF-jB seems to be a central mechanism of tumour cell survival and resistance to apoptosis. 24,25,35,36 The NF-jB family of transcription factors, including RelA (p65), RelB, c-Rel, p50 ⁄p105 (NF-jB1) and p52 ⁄p100 (NF-jB2), regulates a wide variety of cellular processes with important functions in inflammation, apoptosis, proliferation and angiogenesis. 13 In the cytoplasm NF-jB is bound to its inhibitor IjBa, and its activation is mediated by proteasomal degradation of IjB.…”
Section: Discussionmentioning
confidence: 99%